EFFECTIVE LANGUAGE TEACHING USING MODERN METHODS IN SCHOOL PRACTICE. (Ustozlar uchun, 2025)
The modern method of teaching English is based on the classical method of learning foreign languages. However, the psychological aspect, foreign cinema, information technology influenced him. English teaching methods used 20 years ago were more reproductive in nature. Learn the words, read the text, listen to the audio recording, write a letter -the tasks given by the teacher looked like this. Perhaps for this reason, most adults who have studied the language for many years can read and write English but have difficulty speaking it. This article delves into the key modern methods that enhance language teaching effectiveness in school practice, focusing on communicative language teaching, task-based learning, the integration of technology, and the promotion of cultural awareness.